User Behaviour Analysis for the Merchandises Fairness Evaluation - A. Al-Sultany, Ghaidaa; Mohammed Hussain, Saba (International Journal of Engineering and Technology, 2018)
The development of digital technology leads to expansion of advertisements of goods and purchases online. The customer reviews and opinions affect in an essential way on the promotion of products and its reputation. In this paper, for the sake of distinguishing the user behavior in terms of his fairness and bias to the purchased merchandises, the user history has been analyze for extracting crucial features (Extreme rating, productâ€™s goodness, and userâ€™s past reviews). The extracted features help economic companies to exclude biased reviews for the fairness purposes of the evaluation of the product.Â In addition, they bring to light the identity of the user according to his past ratings and reviewing on purchased goods. The experiments in the research have shown encouraging results with respect to the values of the extracted features.Â Â Â Â Â Â Â Â Â Â